Contemporary Spanish cinema - Jordan, Barry, 1950-; Morgan-Tamosunas, Rikki (Manchester Film Studies, 2019)
'Contemporary focus, right up to date with material from 1980s and 90s. Wide-ranging analyses of major directors, themes, genres and issues, including historical film, genre cinema, women in film and autonomies' --Back cover.